1982
DOI: 10.3109/00498258209038945
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of microsomal cytochrome P-450s

Abstract: 1. Eight different forms of cytochrome P-450 have been purified to electrophoretic homogeneity. Electrophoretic, spectral and catalytic properties of these cytochrome P-450s are presented and comparison is made with preparations presented elsewhere in the literature. 2. The levels of these forms of cytochrome P-450 present in liver microsomes of rats treated with various compounds have now been quantified. Several forms of cytochrome P-450 are induced, in a more or less coordinate manner, while levels of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(61 citation statements)
references
References 82 publications
1
59
1
Order By: Relevance
“…Measurement of Cytochrome P450 Content-The CYP contents of mitochondrial and microsome membranes were measured by the difference spectra of carbon monoxide (CO)-treated and dithionite-reduced samples as described by Omura and Sato (57,58) and as modified by Guengerich (59,60), using a dual beam spectrophotometer (Cary 1E; Varian, Walnut Creek, CA). Mitochondrial or microsomal (0.4 mg) proteins were solubilized in potassium phosphate buffer (0.1 M, pH 7.4) containing 1 mM EDTA, 20% glycerol (v/v), sodium cholate (0.5%, w/v), and Triton N-101 (0.4%, w/v).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of Cytochrome P450 Content-The CYP contents of mitochondrial and microsome membranes were measured by the difference spectra of carbon monoxide (CO)-treated and dithionite-reduced samples as described by Omura and Sato (57,58) and as modified by Guengerich (59,60), using a dual beam spectrophotometer (Cary 1E; Varian, Walnut Creek, CA). Mitochondrial or microsomal (0.4 mg) proteins were solubilized in potassium phosphate buffer (0.1 M, pH 7.4) containing 1 mM EDTA, 20% glycerol (v/v), sodium cholate (0.5%, w/v), and Triton N-101 (0.4%, w/v).…”
Section: Methodsmentioning
confidence: 99%
“…Immunochemical quantification of P-450 male and P-450-female: A peroxidase staining technique coupled with SDS-polyacrylamide gel electrophoresis (Western blot) was used to quantitate the content of P-450-male and P-450-female in hepatic microsomes (5,22). The characteristics of P-450-male, P-450 female and monospecific antibodies to these cytochromes were described previously (9,22).…”
Section: Animalsmentioning
confidence: 99%
“…of) cytochromes P450 (Guengerich et al, 1982;Beaune et al, 1986;Kaminsky, 1989). Various P450 isozymes, displaying different regio-and stereoselectivities, have been shown to be involved in the metabolism of warfarin (Guengerich et al, 1982;Rettie et al, 1992). The variety of warfarin metabolizing P450 isozymes offers an explanation for the stereoselective (pharmacokinetic) drug-interactions with R-warfarin (Choonara et al, 1986;Toon et al, 1987;Sutfin et al, 1989;), S-warfarin (Lewis et al, 1974;O'Reilly, 1980), as well as non-stereoselective interactions (O'Reilly et al, 1987) that have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…of) cytochromes P450 (Guengerich et al, 1982;Beaune et al, 1986;Kaminsky, 1989). Various P450 isozymes, displaying different regio-and stereoselectivities, have been shown to be involved in the metabolism of warfarin (Guengerich et al, 1982;Rettie et al, 1992).…”
Section: Introductionmentioning
confidence: 99%